Increasing the Role of BUMDes in Empowering Micro and Small Economies in Sisalak Village, Cisarua District, Sumedang - Wiradirja, Imas Rosidawati; sari, Wahyu Purnama; Noor, Iemas Masitoh; Cristin Sepina; Maharani, Neng Elsa Cika (Jurnal Pengabdian Tri Bhakti, 2024)
Village-Owned Enterprises (BUMDes) is village business entities managed by the community and village government to strengthen the village economy, established based on the needs and potential of the village. BUMDes serve as a pillar of economic activity in the village, functioning as both a social institution and a commercial institution. The role of BUMDes can act as a support system for empowering the village community's economy. One example of a village that partners with BUMDes in improving the community's economy is Cisalak Village. Located in the Cisarua Subdistrict, Sumedang Regency, Cisalak Village currently consists of 19 Micro and Small Enterprises (UMK), distributed administratively across four hamlets: Baranangsiang Hamlet, Sukalaksana Hamlet, Cisalak Hamlet, and Marasa Hamlet. The village is home to 4,028 residents, organized into 29 neighborhood units (RT) and 8 community units (RW). The main objective of this Community Service Program (PKM) is to enhance the role of BUMDes so that it can actively and effectively empower the village, particularly the UMK actors. To achieve this, various stakeholders need to be involved as part of the solution. For example, higher education institutions can act as mentors for BUMDes, providing innovations in management and other areas. Additionally, efforts to enhance the capacity of UMK actors through various training and mentoring programs are essential.